Active Learning and Professional Citizenship in Nursing Education: A Structural Account - Maria Efstathiou; Mary Gouva; Elena Dragioti (Nursing Philosophy, 2026)
ABSTRACT Active learning and professional citizenship are widely discussed in nursing education, yet the conditions under which they converge have not been theoretically specified. In this paper, we advance a structural account of that relation, drawing on deliberative theory, philosophy of education, and nursing scholarship. The relation we describe is one of shared enabling conditions rather than causal production: active learning and professional citizenship converge not because one produces the other, but because each depends on arrangements that require public justification through reasons, engagement with competing claims, and answerability for the consequences of action. We trace a conceptual movement from professional accountability to professional citizenship, and from participatory learning to deliberative practice, specifying a set of conditions that can be instantiated in nursing education but have rarely been theorised as the basis of this relation. In doing so, we give theoretical form to a relation more often enacted than articulated.